The Poisoned City: Flint's Water and the American Urban Tragedy by Anna Clark (review) - Njoku, Anuli (Michigan Historical Review, 2019)
Book Reviews 125 All of the above and more are detailed by Claerbaut. He also covers Michigan State’s program as it went into decline in the late 1960s. Daugherty began to miss on the recruiting trail. At the same time, African American students and athletes on campuses across the nation more vocally joined the civil rights protest movement. It was a difficult period for Daugherty, who never sought credit for his progressive attitudes of providing black athletes equal opportunities. One of his responses was to break more barriers with black assistant coaches. Sherman Lewis, Daugherty’s first Underground Railroad All-American as a halfback from Louisville, Kentucky, joined the MSU staff in 1969. Raye was hired part time in 1971 and full time in 1972. Raye and Lewis went on to the National Football League as assistant coaches and offensive coordinators. A consequence of Daugherty doing what was right without seeking credit allowed myths surrounding a 1970 game matching USC and the University of Alabama to usurp his far more significant role. That is reason to link Daugherty with the words of David Maraniss, the Pulitzer Prizewinning biographer, who wrote, “History writes people out of the story. It’s our job to write them back in.” Thus, until that national trip-wire is no longer stepped over and subsequently triggered, the more the merrier to rightly place Daugherty’s story back into history. Tom Shanahan Author, Raye of Light Anna Clark. The Poisoned City: Flint's Water and the American Urban Tragedy. New York: Metropolitan Books, 2018. Pp. 305. Index. Notes. Cloth: $30.00. Journalist Anna Clark provides a gripping, thought-provoking, and comprehensive account of the people who caused, suffered from, and exposed the Flint water crisis. Clark’s brilliant story reminds us of the farreaching , devastating effects of lead exposure and that safe, high-quality drinking water is essential to good health. Clark meticulously details how corruption, recklessness, and arrogance of public officials, prejudice, and greed characterized the crisis in Flint. The Poisoned City is divided into three parts, each subdivided into several chapters. Part one reviews how water that blessed the indigenous Ojibwa people would eventually curse Flint residents. We learn how industrialization coincided with mistreatment and development of waterways. Vast, ferocious Lake Huron served as Flint’s freshwater 126 The Michigan Historical Review source for nearly 50 years. Amid financial distress, Flint switched to the Flint River water system in April 2014. The new water treatment program lacked corrosion control, breaking federal law. Adding to Flint’s woes were exorbitant water and sewer bills, an aging water infrastructure, and decreased federal funding. Clark also describes the federal government’s alarming apartheid approach to city building. Vicious, systematic tactics prolonged residential segregation and created multigenerational housing inequalities. Desegregation triggered a large-scale departure of whites. In 2014, General Motors (GM) workers noticed water-corroded engine parts. People wondered what it did to the inside of humans. Part two discusses the damaging health effects of and countless sources of exposure to lead. We meet longtime GM research director and leaded gasoline creator Charles Kettering. We gain insight into leaded gasoline’s profitability, Flint’s re-engineering to favor automobiles, fierce rebuttals to decries of lead hazards, ethical burdens of proving lead toxicity, the lead industry’s massive lobbying, and victim-blaming in response to residents’ concerns. Clark discusses loopholes in lead restriction policies, manipulation of lead testing, and a trend of childhood lead poisoning in shrinking cities. We learn how biochemist Marc Edwards, veteran journalist Curt Guyette, regulations manager Miguel Del Toral, pediatrician Mona Hanna-Attisha, and local residents rallied to spur a movement to urge governmental action. We also see effects of a very expansive law signed in 2011 that gave emergency managers unyielding power. Part three details the switch back to Detroit water in October 2015 and the flawed, hasty decision-making of untrustworthy leaders. Governor Rick Snyder declares a state of emergency in January 2016 and announces a two-year Legionnaire’s disease outbreak. Declaration of a federal emergency in Flint follows. A myriad of lawsuits, rebuttals, indictments, and pushbacks ensues. Apologies are offered, promises are made, and secrecy and injustices proliferate. Sadly, accountability...
Keywords: book.review; dept.pch